The development Special physical training of the servicemen of the Interior Troops of MIA Ukraine in the combat training system - Khatsayuk, О. V. (Honor and Law, 2019)
This article highlighted the technology of the development of Special physical training training of the servicemen of the Interior Troops of MIA Ukraine in the combat training system using such modern technical ways of study. In the result of long period of pedagogical experience was proven the modern scientific instrumentary.